Self-control and problematic use of social networking sites: Examining distress tolerance as a mediator among Argentinian college students - Pilatti, Angelina (2021)
Introduction: Use of Social networking sites (SNSs) is a highly prevalent behavior worldwide and, for some individuals, its use can turn maladaptive. There has been growing interest to identify which variables are associated with problematic use of SNSs. Aim: The present study cross-sectionally examined whether the associations between different features of self-control (i.e., impulsivity-like traits, self-regulation and emotion regulation) indirectly relate to two outcomes of SNSs (hours of use and problematic use) via distress tolerance. Methods: A sample of 509 Argentinean college students (70.3% female; Mean age = 21.15 ± 5.15) completed an online survey. Results: Two significant indirect effects were found: a) higher negative urgency was associated with higher problematic use of SNSs via lower distress tolerance and b) higher self-regulation was associated with lower problematic use of SNSs via higher distress tolerance. Positive urgency, negative urgency and self-regulation had significant direct associations with problematic use of SNSs while neither component of emotion regulation was significantly associated with SNSs outcomes. No significant direct or indirect effects were found between any of the self-control features and time spent using SNSs. Conclusions: The results highlight dysfunctional self-control, particularly emotion-driven impulsivity and low self-regulation, as relevant components of maladaptive SNSs that seem to operate by decreasing the perceived capacity to tolerate negative affect. In this context, interventions targeting the development and improvement of distress tolerance abilities might have a positive impact on problematic use of SNS.